Бюджетний дефіцит України: сутність, причини виникнення та особливості управління - Коляда, Тетяна Анатоліївна; Косминіна, Олена Сергіївна (Modern Economics, 2018)
У статті досліджено економічну сутність бюджетного дефіциту як перевищення видатків бюджету над його доходами, причини та джерела його виникнення. Розглянуто поняття бюджетного дефіциту і динаміку дефіциту державного бюджету України у 2013-2017 рр., визначено причини та фактори його зростання, проаналізовано методи скорочення дефіциту бюджету у Європейських країнах. Запропоновано можливі заходи щодо мінімізації дефіциту бюджету України, а саме такі, що, з одного боку, стимулювали б приплив коштів у бюджетний фонд країни, а з іншого боку – сприяли скороченню державних витрат.

Introduction. The аrtісlе аnаlуzеs thе есоnоmіс еssеnсе оf thе budgеt dеfісіt аnd thе rеаsоns fоr іts оссurrеnсе. Thе соnсерt аnd dуnаmісs оf thе stаtе budgеt dеfісіt in Ukrаіnе аrе соnsіdеrеd, thе rеаsоns оf іts grоwth аrе dеtеrmіnеd. Роssіblе mеаsurеs tо minimize budget dеfісіts аrе рrороsеd. Purpose. The purpose of this article is to investigate the economic essence of the budget deficit, to reveal the causes of its occurrence and to determine the peculiarities of their management at the current stage of development in Ukraine. Results. The article analyzes the economic essence of the budget deficit, determines the reasons for its occurrence, namely: inflation processes, currency unbalancing and settlement systems, imperfect investment, tax and credit policy, features of the budget deficit management at the present stage of development in Ukraine. Conclusions. For stabilization of the economy, it is necessary to solve a number of problems: the decline of production, the difficult financial situation of the country's enterprises, the crisis of non -payment, non-payment of taxes, which, as a result, lead to a budget deficit in Ukraine. In the process of overcoming the budget deficit in our country, it is inappropriate to apply reductions in social spending and to increase the tax burden. Given the current situation, one must understand that such measures will lead to worsening socio-economic situation in Ukraine and lead to mass discontent among the population. Recently, one can observe a high level of inflation, an unstable political situation, hostilities in eastern Ukraine, and the implementation of various state reforms that require large material costs. All this is very depleting for the economy of our country and makes it impossible to raise taxes and reduce spending on the social sphere. The program of concrete measures to reduce the budget deficit should include and consistently implement such measures, which, on the one hand, will stimulate the inflow of funds into the budget fund of the country, and on the other hand, will contribute to the reduction of public expenditures. Here are the following measures: – change of investment directions of budgetary funds in the field of the national economy in order to increase significantly the financial returns of each hryvnia; – reduction of military expenses; – keeping funding for only the most important social programs, a moratorium on the adoption of new social programs that require significant budget funding; – the prohibition of the National Bank to provide loans to government structures of any level without proper execution of debts with government securities. It should be noted that in our country, in modern conditions, the practice of balancing the budget on a non–deficit annual basis is unrealistic, due to the lack of financial resources. The deficit in state -owned activities should be oriented towards further development rather than being a source of financing for current expenditures. Because only effective management of the state budget deficit and a balanced debt policy can provide a solid foundation for sustained economic progress and deep structural social and economic transformations in our country.
Keywords: бюджет; дефіцит бюджету; державний борг; доходи бюджету; видатки бюджету; джерела фінансування дефіциту бюджету; budget; deficit budget; state debt; budget revenues; budget expenditures; financing of budget deficit